Who Profits from Ecosystem Services? The Winners and Losers of Forestry PES Schemes in Costa Rica & Beyond - Gurts, Olga (Université d'Ottawa | University of Ottawa, 2015)
Costa Rica’s National Payment for Ecosystem Services (PES) program has been hailed as an example of a successful application of market-based conservation to increase forest cover. The theory and application of PES has greatly evolved since its inception in the mid-1990s, but many questions remain unanswered including the real environmental and social benefits derived from PES schemes, particularly effects on the poor and landless. Using a thorough literature review of forest cover and watershed PES case studies in Costa Rica and other countries in Latin America, this paper reveals that PES benefits have, in most cases, been beneficial as a form of income diversification for larger landowners with insignificant benefits for participants at the very bottom of the socioeconomic pyramid. Suggestions for evolution of the PES framework include incorporation of greater and more diverse incentives, social and environmental targeting as well as improving awareness of PES effectiveness at the local level. More broadly, the PES framework has been useful in testing the grounds for market-based conservation with state participation while promoting a culture of sustainable ecosystem use within socioeconomic boundaries.